Islamic Reform Movements after the Arab Spring (American Journal of Islam and Society, 2013)
On June 24-July 3, 2013, the International Institute of Islamic Thought heldits annual Summer Institute for Scholars. Given the number of presentations,only a few of them will be mentioned here.In his welcoming remarks, Abdul Aziz Sachedina (George Mason University)spoke eloquently about how change has to come from within, howpolitics still dominates values, and how the Qur’an and Sunnah are being readnot for inspiration, but for putting down opposition and dissenters. The ArabSpring represents a challenge to undertake such an internal reform. Unfortunately,he said, cyberspace contains no serious conversation in this regard,just hostility and animosity, which only damages Muslims. He called for leadersto “moralize” the entire issue in order to achieve co-existence, mainly betweenShi‘is and Sunnis, and wondered if the reformers could deal with thisand other issues.John Voll (Georgetown University), who delivered the keynote address,“Pop-politics and Elections: Islam and Democracy after the Arab Spring,”raised the question as to whether the Arab Spring makes any difference, giventhat reform movements have been going on in the Muslim world since 1880.Are we, he asked, “looking at something moving forward/different, or just rehashingthe same old arguments?” He opined that a new vocabulary is neededand that people have to move beyond “interfaith,” “tolerance,” and interreligiousdialogue and speak to each other about “shared interests.” He then discussedearlier Muslim reform movements and how their goals have changedover the years.Yahya Michot (Hartford University) presented a special lecture entitled“Taymiyyan Thoughts for a Temperate Arab Summer.” He pointed out howdifferent groups (e.g., those groups responsible for assassinating Sadat, theAlgerian civil war, and 9/11) took Ibn Taymiyyah’s anti-Mongol fatwas outof context to justify their actions. Thus they ignored the underlying issues:The supposedly “Muslim” Mongols were still massacring Muslims; ...